Synergistic action of recombinant accessory hemicellulolytic and pectinolytic enzymes to Trichoderma reesei cellulase on rice straw degradation - Laothanachareon, Thanaporn; Bunterngsook, Benjarat; Suwannarangsee, Surisa; Eurwilaichitr, Lily; Champreda, Verawat (Bioresource technology, 2015)
[Display omitted] •Synergy of accessory hemicellulase and pectinase to core cellulase was shown.•A varying degree of synergism of ARA, PEC, XYL to ACR cellulase was found.•Removal of ara side chain by arabinofuranosidase enhanced cellulase activity.•Synergy of pectin esterase to cellulase mixture was firstly reported.•The quaternary mixture showed 214% glc obtained/FPU compared to ACR alone. Synergism between core cellulases and accessory hydrolytic/non-hydrolytic enzymes is the basis of efficient hydrolysis of lignocelluloses. In this study, the synergistic action of three recombinant accessory enzymes, namely GH62 α-l-arabinofuranosidase (ARA), CE8 pectin esterase (PET), and GH10 endo-1,4-beta-xylanase (XYL) from Aspergillus aculeatus expressed in Pichia pastoris to a commercial Trichoderma reesei cellulase (Accellerase® 1500; ACR) on hydrolysis of alkaline pretreated rice straw was studied using a mixture design approach. Applying the full cubic model, the optimal ratio of quaternary enzyme mixture was predicted to be ACR:ARA:PET:XYL of 0.171:0.079:0.100:0.150, which showed a glucose releasing efficiency of 0.173gglc/FPU, higher than the binary ACR:XYL mixture (0.122gglc/FPU) and ACR alone (0.081gglc/FPU) leading to a 47.3% increase in glucose yield compared with that from ACR at the same cellulase dosage. The result demonstrates the varying degree of synergism of accessory enzymes to cellulases useful for developing tailor-made enzyme systems for bio-industry.